Write, draw, show, and tell: a child-centred dual methodology to explore perceptions of out-of-school physical activity - Robert J. Noonan; Lynne M. Boddy; Stuart J. Fairclough; Zoe R. Knowles (BMC, 2016)
Abstract Background Research to increase children's physical activity and inform intervention design has, to date, largely underrepresented children's voices. Further, research has been limited to singular qualitative methods that overlook children's varied linguistic ability and interaction preference. The aim of this study was to use a novel combination of qualitative techniques to explore children's current views, experiences and perceptions of out-of-school physical activity as well as offering formative opinion about future intervention design. Methods Write, draw, show and tell (WDST) groups were conducted with 35 children aged 10-11 years from 7 primary schools. Data were analysed through a deductive and inductive process, firstly using the Youth Physical Activity Promotion Model as a thematic framework, and then inductively to enable emergent themes to be further explored. Pen profiles were constructed representing key emergent themes. Results The WDST combination of qualitative techniques generated complimentary interconnected data which both confirmed and uncovered new insights into factors relevant to children's out-of-school physical activity. Physical activity was most frequently associated with organised sports. Fun, enjoyment, competence, and physical activity provision were all important predictors of children's out-of-school physical activity. Paradoxically, parents served as both significant enablers (i.e. encouragement) and barriers (i.e. restricting participation) to physical activity participation. Some of these key findings would have otherwise remained hidden when compared to more traditional singular methods based approaches. Conclusions Parents are in a unique position to promote health promoting behaviours serving as role models, physical activity gatekeepers and choice architects. Given the strong socialising effect parents have on children's physical activity, family-based physical activity intervention may offer a promising alternative compared to traditional school-based approaches. Parents' qualitative input is important to supplement children's voices and inform future family-based intervention design. The WDST method developed here is an inclusive, interactive and child-centred methodology which facilitates the exploration of a wide range of topics and enhances data credibility.